Acute hypoxia due to right to left blood shunting in a patient with atrial septal defect - Solař, Miroslav; Fridrich, Jan; Ceral, Jiří; Borovec, Martin (Resuscitation, 2007)
Acute right to left blood shunt is an unusual cause of acute hypoxia. We describe a case of a patient with an atrial septal defect who developed acute hypoxia due to cardiac tamponade. Acute haemopericardium developed as a complication of temporary transvenous cardiac pacing. Bubble contrast echocardiography confirmed right to left blood shunting at the atrial level. Acute hypoxaemia and the right to left blood shunt resolved when the pericardium was drained. The case underscores the importance of evaluating the presence of an intracardial shunt in patients with otherwise inexplicable hypoxia.
Keywords: perikardiální efuze; Cardiac Tamponade; Cardiac Pacing, Artificial; kardiostimulace umělá; srdeční tamponáda; Pericardial Effusion; Heart Septal Defects, Atrial; kontrastní látky; Hypoxia; Aged; Echocardiography; senioři; fatální výsledek; echokardiografie; Fatal Outcome; akutní nemoc; Acute Disease; lidé; Drainage; ženské pohlaví; Contrast Media; Humans; drenáž; Female; defekty septa síní; hypoxie